Primary cervicothoracic melanoma of spinal cord: a case report and literature review - Dang, Ying; Du, Aichao; Wei, Wenyuan; Xue, Jungang (Frontiers in Oncology, 2024)
A 53-year-old male patient presented progressive numbness and weakness in the right limbs for a 2-year duration. Magnetic resonance imaging scans revealed an intramedullary lesion crossed over cervical and thoracic levels accompanied by syringomyelia at the proximal end of the lesion. The patient underwent subtotal resection of the neoplasm. The histological findings of the tumor were consistent with primary intramedullary malignant melanoma and not initial ependymoma after careful dermatologic and ophthalmologic re-examination. Primary melanoma of the spinal cord, particularly cervicothoracic localization with syringomyelia, is seldom reported in the literature. We report a case of this uncommon tumor and also discuss the clinical course, diagnosis, and treatment.